Sistem Monitoring Tempat Sampah Berbasis Wirelles Sensor Network pada Kampus Universitas Kristen Indonesia Toraja - Samrius Upa’; Fikran Fikran; Masrin Tibian; Yulfrani Masak Paembonan; Melda Lospa (Lembaga Pengembangan Kinerja Dosen, 2025)
At the Indonesian Christian University Toraja Campus, there are approximately 8 cleaning services, which will have difficulty handling trash bins spread across each area of ​​the campus, where the cleaning service not only monitors trash bins, but also has other jobs. This can cause delays in handling full trash bins. Prototype of a Wireless Sensor Network-Based Trash Bin Monitoring System at the Indonesian Christian University Campus. Can be a solution to overcome waste management at the Indonesian Christian University Campus. The design for designing a monitoring system uses the fritzing application. and coding using aurdiuno IDE. Using Wemos D1 Mini As data processing and sending using ultrasonic sensors as volume detectors and using arduino for coding. Testing the tool using Black Box testing, and the test results using the Black Box tool were declared successful and several sensors used successfully sent data and were processed by the server and forwarded to the Web using Arduino coding where the Ultrasonic sensor received data and threw data and was assisted by wemos d1 mini to send data that was already connected to the network.